2014
DOI: 10.5455/2349-3933.ijam20141112
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-investigative assessment and comparison of cardiovascular risk factors in young and elderly patients of acute coronary syndrome

Abstract: Background: Coronary artery disease in Indians occurs at an earlier age than most other populations. Risk profile and angiographic severity of young acute coronary syndrome (ACS) patients differ from those in the elderly. Methods: This cross-sectional study included 46 young (≤45 years) and 45 elderly (>45 years) ACS patients. Clinical features, risk factor profiles and coronary angiograms of these patients were studied and compared. Results: Compared with the elderly, more young patients had chest pain and ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…9 , 15 , 16 , 17 , 18 , 19 Hanif et al 20 revealed 29.69 ± 23.50 mg/dl, 43.92 ± 32.69 mg/dl, and 50.15 ± 55.62 mg/dl for healthy controls, elder ACS patients, and young ACS patients, respectively. In line with these findings, Bhattacharjee et al 21 reported LP(a) > 30 mg/dl in 41.3% young ACS patients as compared to 22.2% elder ACS patients. Further, Yusuf et al 22 have also reported increased LP(a) levels to be associated with increased risk of ACS.…”
Section: Discussionmentioning
confidence: 54%
“…9 , 15 , 16 , 17 , 18 , 19 Hanif et al 20 revealed 29.69 ± 23.50 mg/dl, 43.92 ± 32.69 mg/dl, and 50.15 ± 55.62 mg/dl for healthy controls, elder ACS patients, and young ACS patients, respectively. In line with these findings, Bhattacharjee et al 21 reported LP(a) > 30 mg/dl in 41.3% young ACS patients as compared to 22.2% elder ACS patients. Further, Yusuf et al 22 have also reported increased LP(a) levels to be associated with increased risk of ACS.…”
Section: Discussionmentioning
confidence: 54%
“… 105 However, multi-vessel disease is more common in older patients with CAD. 106 , 107 Atherosclerotic lesions in young patients that are present in the LAD and are proximal in location have been identified as important determinants of low left ventricular ejection fraction, which in turn increases mortality in STEMI. 108 According to our review, the common complications in young patients with CAD were heart failure, cardiogenic shock, arrhythmias, and mechanical complications.…”
Section: Discussionmentioning
confidence: 99%